Antimicrobial Activity of Leaf and Bark Extracts of Cassia fistula - Prabagar, S.; Nanthakumar, J.; Thuraisingam, S.; Prabagar, J. (Research gate, 2020)
Cassia fistula L is a medium sized tree and its parts are used in folk medicines for bacterial and fungal diseases. Aqueous extraction of plant materials such as leaf and bark were investigated for anti-microbial property without changing concentration. Results of this study revealed that all extracts had good inhibitory activity against gram positive and gram negative bacteria. The clear zone for Staphylococcus aureus and E. coli were found with the diameter of 2.5 cm and 2.9 cm respectively, though the inhibitory diameter of Staphylococcus aureus was smaller than the streptomycin control. Antifungal activity of bark and leaf extract of C. fistula against Aspergillus showed the highest inhibitory growth (64.3%). The findings exhibit that leaf and bark extracts have broad spectrum activity and there is a possibility in treatment of infectious diseases.
Keywords: Cassia fistula; Leaf and Bark Extracts; Antimicrobial Activity